2012
DOI: 10.1002/jmv.23324
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of sustained virological response in Greek and Egyptian patients with hepatitis C genotype 4: Does ethnicity matter?

Abstract: Hepatitis C virus genotype 4 (HCV-4) is spreading beyond Africa and the Middle East but data regarding treatment with pegylated interferon alpha and ribavirin of European populations infected with HCV-4 remains limited. Interestingly, European (vs. Egyptian) origin has been associated with lower sustained virological response rates. Hence the aim of this study was to investigate the treatment outcomes of Greek (vs. Egyptian), treatment-naïve patients infected with HCV-4 (subtype a) and to identify factors infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 36 publications
3
13
1
Order By: Relevance
“…In Greece, prevalence of genotype 4 is amongst the highest reported within Europe, estimated around 15% [18][19][20][21][22]. Similarly, a percentage of 14.7% was confirmed in our study cohort of consecutive HCV patients.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In Greece, prevalence of genotype 4 is amongst the highest reported within Europe, estimated around 15% [18][19][20][21][22]. Similarly, a percentage of 14.7% was confirmed in our study cohort of consecutive HCV patients.…”
Section: Discussionsupporting
confidence: 85%
“…In Greece, genotype 4 accounts for about 15% of all HCV infections [18][19][20][21][22] and is generally considered as "difficult to treat" in everyday clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…The polymorphism rs12979860 had the highest predictive value of SVR compared with rs11881222 and rs8099917, and the CC genotype of rs12979860 had the highest predictive value in genotype 4. Moreover, the multivariate regression analysis showed that the rs12979860 SNP was the only SNP associated with clearance, whereas the other SNPs ceased, confirming that this association was based on a single signal (Papastergiou et al, 2012).…”
Section: Discussionmentioning
confidence: 54%
“…Higher age, advanced liver fibrosis, and diabetes have been shown to significantly reduce the response rates in patients infected with HCV-4, and Egyptian ethnicity has been claimed to be a positive predictor of a sustained virological response (Papastergiou et al, 2012) that is not related to insulin resistance (Cieśla et al, 2012). Serum adiponectin at baseline levels appears to be an independent predictor in the achievement of SVR in Genotype 4 (Derbala et al, 2009).…”
Section: Introductionmentioning
confidence: 88%
“…The majority of studies (40/51, 78%) originated from the Middle East[1013, 15, 16, 18, 27, 28, 34, 35, 37, 4042, 45, 46, 53–56, 59, 62, 63, 66, 67, 69, 72, 75, 78, 80, 81, 8385, 88, 91, 95] and Europe (9/51, 18%)[14, 38, 39, 65, 71, 76, 79, 93, 96]. One originated in Cameroon[77] and one multi-center study was conducted in 19 countries[73].…”
Section: Resultsmentioning
confidence: 99%